HUBUNGAN DUKUNGAN SOSIAL DAN KUALITAS TIDUR DENGAN TINGKAT STRES PADA MAHASISWA KESEHATAN MASYARAKAT UPN VETERAN JAKARTA SELAMA PJJ DI ERA COVID-19 TAHUN 2020 - Sara Aliah Rachman (2021)
Stress is a pressure that can disrupt the balance of the body. Poor sleep quality and lack of social support can cause stress for students. Task load is one of student lamentations during the implementation of distance learning so that students have to spend a lot of time in completing their tasks and causes students to delay their sleep. Moreover, students need social support to motivate them to complete their tasks. This study aimed to find out the relationship between social support and sleep quality with stress levels in UPN Veteran Jakarta Public Health students during PJJ in COVID-19 Era in 2020. This study used a Cross-Sectional approach. The population was students of the public health major in UPN Veteran Jakarta with a large sample of 260 people. The research instruments used were DASS 42 stress subscale, PSQI, and MSPSS. Data analysis in this study were univariate analysis and bivariate analysis with Chi-Square. This study results showed that there was no relationship between social support and stress levels (p-value>0,05). Whereas there was a relationship between sleep quality and stress levels (p-value<0,05). Therefore, students are encouraged to manage their bedtime and learn how to manage stress well.